ANALISIS TINGKAT KEPUASAN PETANI TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN DI KABUPATEN KONAWE UTARA (Analysis of Farmers Satisfaction Level Towards the Performance of Field Agricultural Extension Workers in North Konawe District) - Rizki, Selvi Diliyanti; Rosmalah, Sitti; Mustam, Mustam; Sondeng, Sabaruddin; Nurmaya, Nurmaya (Jurnal Ilmiah Sosio Agribis, 2025)
This research was carried out in North Konawe Regency in June-July 2024. This research aims to identify the quality of service attributes based on the level of importance and performance of extension workers according to farmers, analyze the level of conformity between the importance of attributes for farmers and the performance of extension workers, and find out how satisfied farmers are with performance. agricultural extension in North Konawe Regency. The research area was determined purportively. The data analysis technique used is qualitative and quantitative descriptive analysis, using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. Based on the research results, the highest level of conformity between the interests of farmers and the performance of extension workers is found in the attribute of instructors helping farmers to make administration of RDKK proposals, administration books, and monthly reports, amounting to 88.51%, which means it is appropriate, and the lowest level of conformity is found in the attributes of extension agents serving and completing the problem completely was 46.23%. The results of the analysis of the level of farmer satisfaction with the performance of agricultural instructors were 50.51%, which means they are quite satisfied.Keywords: Importance and Performance of Extension Workers, IPA, CSI.